Patient with Helsmoortel-van der Aa Syndrome and O’Donnell-Luria-Rodan Syndrome: a case report - Medeiros, Ana Beatriz Deleame; Coutinho, Danillo Alencar; Alarcón, Rafael Patricio dos Santos; Carvalho, Andrea de; Praxedes, Leide de Almeida (Brazilian Journal of Case Reports, 2023)
Heterozygous pathogenic variants in the ADNP gene cause Helsmoortel-van der Aa syndrome which is an autosomal dominant mutation, whose patients have autism spectrum disorder (ASD) and intellectual disability. Pathogenic variants in the KTM2E gene are related to O’Donnell-Luria-Rodan syndrome, also autosomal dominant, characterized by global development delay. The case of a male patient, only child, born at term measuring 45 cm (z-1) and weighing 2.460 kg (z-2) was described. The patient presented short stature, autism spectrum disorder, delay in neuropsychomotor development, gastrointestinal reflux, hyperopia, recurrent infections, and constipation. The result from whole exome sequencing (WES) identified two variants of uncertain significance (VUS) in the ADNP and KMT2E genes, whose syndrome related in literature have compatible signs and symptoms with those found in the patient.